Canada's Compassionate Care Benefit: Is it an adequate public health response to addressing the issue of caregiver burden in end-of-life care? - Cohen S Robin; Vuksan Mirjana; Giesbrecht Melissa; Stajduhar Kelli; Crooks Valorie A; Eby Jeanette A; Williams Allison M; Brazil Kevin; Allan Diane (BMC, 2011)
Abstract Background An increasingly significant public health issue in Canada, and elsewhere throughout the developed world, pertains to the provision of adequate palliative/end-of-life (P/EOL) care. Informal caregivers who take on the responsibility of providing P/EOL care often experience negative physical, mental, emotional, social and economic consequences. In this article, we specifically examine how Canada's Compassionate Care Benefit (CCB) - a contributory benefits social program aimed at informal P/EOL caregivers - operates as a public health response in sustaining informal caregivers providing P/EOL care, and whether or not it adequately addresses known aspects of caregiver burden that are addressed within the population health promotion (PHP) model. Methods As part of a national evaluation of Canada's Compassionate Care Benefit, 57 telephone interviews were conducted with Canadian informal P/EOL caregivers in 5 different provinces, pertaining to the strengths and weaknesses of the CCB and the general caregiving experience. Interview data was coded with Nvivo software and emerging themes were identified by the research team, with such findings published elsewhere. The purpose of the present analysis was identified after comparing the findings to the literature specific to caregiver burden and public health, after which data was analyzed using the PHP model as a guiding framework. Results Informal caregivers spoke to several of the determinants of health outlined in the PHP model that are implicated in their burden experience: gender, income and social status, working conditions, health and social services, social support network, and personal health practises and coping strategies. They recognized the need for improving the CCB to better address these determinants. Conclusions This study, from the perspective of family caregivers, demonstrates that the CCB is not living up to its full potential in sustaining informal P/EOL caregivers. Effort is required to transform the CCB so that it may fulfill the potential it holds for serving as one public health response to caregiver burden that forms part of a healthy public policy that addresses the determinants of this burden.